ESTIMASI KEDALAMAN KERAK BUMI DI JAWA TENGAH BERDASARKAN WAKTU TEMPUH GELOMBANG SEISMIK MENGGUNAKAN TEORI SINAR - , Titan Parasita Siradj, S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
An estimation of crustal depths in Central Java based on seismic wave travel time using Ray Theory has been done. This research uses the data of South Sumatraâs earthquake on 25th July 2004 at 14.35.18 UTC (universal time coordinate). The data used as a reference is the data of observed travel time that is defined as the first arrival time of an earthquake wave recorded by station. The estimation is done by making travel time modeling whose results will be fitted with the observed travel time to know how fit the models used are. The models which are constructed are two-layer medium model, three-layer medium model and modified two-layer medium model. The best result with very small error value, which is kin to zero, is obtained from the modified two-layer medium model. This accuracy gives a fitting curve which is almost the same between the observed and modeled travel time. Comparing to other model, a ray trace method which also has small error values has been done. These small errors are described by correlative coefficients which are close to unity. The modeled travel time resulted is used to estimate the crustal depth in Central Java and gives values ranging from 24 km to 30 km with crustal depth average of 26,65 km. Key words : seismic wave, crustal depth, travel time